The impact of Islamic moderation method in establishing social peace in Kurdistan = أثر منهج الوسطيَّة الإسلاميَّة في ترسيخ السِّلم الاجتماعي في كردستان - Arif, Arif Ali; Ismael, Ardawan Mustafa (Usuli Faqih Research Centre, 2016)
تهدِف فكرة البحث إلى تبيان أثر منهج الوسطية الإسلامية في ترسيخ ال س لم الاجتماعي، وطرحها وفق المناهج العلمية. وقد انتهج الباحثان في الكتابة المنه ج الاستقرائي؛ لاستقراء النصوص القرآنيَّة، والأحاديث النبوية؛ من أجل تأصيل منهج الوسطية الإسلامية. وكذلك المنهج التحليلي الوصفي؛ لتحليل النصوص وتوصيفها. وقد أبان البحث أنَّ الوسطية هي الاعتدال، والاعتراف بالطرف المقابل، وإعطاء كل طرف حقه، دون حيفٍ ولا طغيانٍ ، وأنَّ السلم الاجتماعي عبارةٌ عن المظاهر الإيجابية في المجتمع، وإزالة المظاهر السلبية فيه.كما أوضح أنَّ القرآن الكريم والحديث النبوي قد رسخا مبادىء الوسطية، وحرَّضا المسلمين على انتهاج منهجه، وكشف أنَّ من خصائص هذا المنهج ابتناءه على العدل والحكمة، واليسر المنضبط. وأنَّ للوسطية آثارًا محمودةً على أفراد المجتمع، وأن إقليم كردستان العراق ممثلاً بشعبه الأصيل قد انتهج منهج التعايش السلمي بين مك وِنات الشعب المختلفة، وكان للخطاب الإسلامي ممثلاً بالمؤسسات الدينية في الإقليم دورٌ حيوي في ترسيخ مفاهيم الوسطية في قلب وعقل الفرد الكردي؛ كالتسامح، والتعايش، ونبذ الإ رهاب، والتطرف. وإنَّ منهج الوسطية هو الذي يجعل الاختلاف الفقهي أرضًا خصبةً؛ قصد التقريب بين المذاهب المختلفة، ومصدر عطاءٍ لمستجدَّات الحياة، لا سبيلاً لتراشق الاتهامات، وته ج م كل فريقٍ على الآخر، وتعصبٍ أعمى لمن ينتمي إليه. The research aims to demonstrate the impact of Islamic moderation method in the establishment of social peace, and in putting it in accordance with the scientific curriculum. The researchers adopts the inductive method; to extrapolate Quranic texts and hadith; in order to consolidate the Islamic approach of moderation. Similarly, the researchers employs descriptive analytical method; for textual analysis and characterization. The research’s outcome has shown that al-wasatiyyah is moderation, i.e. to recognize the opposite partyby giving each party the right it deserved, without injustice and tyranny. The social peace is a positive manifestations in society, and in removing the negative aspects. The research also explained that the Quran and the Hadith have established the principles of moderation, incited Muslims to adopt the method and revealed that the characteristics of this approach were built on justice, wisdom, convenience and discipline. It shows also that moderation has undesirableeffects on community members, and that the Kurdistan region of Iraq which represented by its authentic people had pursued a method of peaceful coexistence between the different components of the people, and the Islamic discourse which represented by religious institutions in the region have a vital role in consolidating the moderation concepts in the heart and mind of the Kurdish individual; such as tolerance, coexistence, and renunciation terrorism and extremism. The moderation approach is the one which makes the fiqh difference fertile ground; inadvertently bring the different sects, and the source of a tender for the developments of life, not a way to an exchange of accusations and attack each team over the other, and bigotry to those who belong to it.